An effect of chiral dopants on mesomorphic and electro-optical properties of ferroelectric smectic mixture. Issue 15 (8th December 2019) - Gaładyk, Katarzyna; Piecek, Wiktor; Czerwiński, Michał; Morawiak, Przemysław; Chrunik, Maciej; Raszewski, Zbigniew
ABSTRACT: The aim of the presented research was an assessment of an effect of chiral dopants on the physical and electro-optical properties of a ferroelectric smectic mixture which is a key factor of elaboration of working ferroelectric liquid crystal (FLC) mixtures of tailored properties, especially with the tilt angle θ value near 22.5° in a broad temperature range. Testing FLC mixtures were prepared using the common pyrimidine-based parent mixture F4 doped with three different chiral dopants. The thermal characteristic of the optical tilt angle θ O P T, tilt angle calculated by means of X-ray diffraction method θ X R D, spontaneous polarisation P s and layer spacing d of obtained FLC mixtures were studied. Based on the above measurements and computer calculations, the relationship between spontaneous polarisation P s and tilt angle θ O P T was discussed. Electro-optical performance of the Surface Stabilised Ferroelectric Liquid Crystal (SSFLC) structures was observed. The relation between the molecular properties of chiral dopants and the electro-optical and physical properties of obtained FLC mixtures is considered in frames of the extended microscopic model of the spontaneous polarisation in FLCs. Graphical abstract: